Ocular Motor Score (OMS): a clinical tool to evaluating ocular motor functions in children. Intrarater and inter‐rater agreement. (6th March 2015) - Olsson, Monica; Teär Fahnehjelm, Kristina; Rydberg, Agneta; Ygge, Jan
Abstract Purpose Ocular motor score (OMS) is a new clinical test protocol for evaluating ocular motor functions in children and young adults. OMS is a set of 15 important and relevant non‐invasive ocular motor function parameters derived from clinical practice. The aim of the study was to evaluate OMS according to intrarater and inter‐rater agreement. Methods Forty children aged 4–10 years, 23 girls median age 6.5 (range 4.3–9.3) and 17 boys median age 5.8 (range 4.1–9.8) were included. The ocular motor functions were assessed and scored according to the OMS protocol. The examinations were videotaped. To obtain the intrarater agreement, the first author examined and scored the children twice, first in the clinic and 2 weeks later by watching the videotape. To obtain the inter‐rater agreement, three other raters independently scored the ocular motor function of the children by watching the videotapes. Results The overall observed intrarater agreement was 88%, and the observed inter‐rater agreement between the three raters was 80%. For none of the subtests was there an observed intrarater agreement lower than 65%. Three of the subtests had an observed inter‐rater agreement of 65% or below. Conclusion Overall there was high observed intra‐ and inter‐rater agreement for the OMS test protocol. Subtests such as saccades and smooth pursuit were more difficult for raters to score similarly according the clinical OMS test protocol.